Sexual and Reproductive Health and Rights in India Self-care for Universal Health Coverage - Pachauri, Saroj; Pachauri, Ash; Mittal, Komal (SpringerBriefs in Public Health,, 2022)
This open access book addresses self-care on sexual and reproductive health and rights and HIV prevention and treatment in the most marginalized and vulnerable communities. Case studies and personal narratives are used to share their perspectives and experiences, sources of information for self-care products, motivations for self-care, and challenges and outcomes. Self-care provides the way to reach the last mile in achieving universal health coverage and the Sustainable Development Goals. Issues related to stigma, discrimination and violence among these communities are highlighted. Changes in policies and programs to improve their sexual and reproductive health, education and employment are discussed. The last chapter in the book examines how the agenda on self-care can be advanced in the years ahead. The audience for this publication includes health professionals, researchers, those managing health institutions and service providers.